Mutually Enhancing Responsibility: A Theoretical Exploration of the Interaction Mechanisms Between Individual and Corporate Moral Responsibility - Constantinescu, Mihaela (Journal of business ethics, 2015)
Moral responsibility for outcomes in corporate settings can be ascribed either to the individual members, the corporation, or both. In the latter case, the relationship between individual and corporate responsibility has been approached as inversely proportional, such that an increase in individual responsibility leads to a corresponding decrease in corporate responsibility and vice versa. In this article, we develop a non-proportionate approach, where, under specific conditions, individual and corporate moral responsibilities interact dynamically, leading to a mutual enhancement of responsibility: the more the corporation is responsible, the more the individuals become responsible and vice versa. We develop this mutually enhancing approach in terms of normative ascriptions of responsibility, while leaving aside empirical implications in terms of mutual awareness of responsibility between individuals and corporations. We explore conceptually the conditions and mechanisms that generate this mutual enhancement and also discuss the implications for research and practice.